Charting a course for marine sustainability: legal and policy coordination in developing countries amidst trade and shipping turbulence - Niu, Qi; Xing, Wang (Frontiers in Marine Science, 2025)
IntroductionTrade fluctuations and maritime sanctions have a range of potential adverse impacts on the maritime sector, including port congestion, operational restrictions, fuel supply disruptions and others, leading to increased fuel consumption and higher pollutant emissions, and even a greater risk of marine pollution incidents, further challenging marine sustainability. Developing countries, especially Least Developed Countries (LDCs), Landlocked Developing Countries (LLDCs), and Small Island Developing States (SIDS), are particularly vulnerable to such trade and shipping turbulence. This study aims to explore how developing countries can leverage multilateral legal frameworks to advance marine environmental protection in response to the challenges posed by trade and shipping turbulence, focusing on enhancing legal and policy coordination under international law. Specifically, the study addresses the following key questions: (1) how trade and shipping turbulence generates regulatory and compliance risks that threaten marine sustainability; (2) how developing countries can strengthen their legal and policy coordination within the International Maritime Organization (IMO); (3) how developing countries can align trade and marine environmental goals in the World Trade Organization (WTO); (4) how developing countries can reinforce port state and flag state control as legal enforcement tools; (5) what differentiated legal and policy recommendations can be drawn for LDCs, LLDCs, and SIDS.MethodsThis study employs a combination of literature reviews and case study analyses to explore how developing countries can strengthen legal and policy coordination within the IMO and WTO frameworks, and through port and flag state regulatory cooperation. Existing literature, policy documents and relevant international cases are analyzed to identify best practices and examine the challenges and opportunities for developing countries.ResultsThe analysis concludes that achieving marine sustainability requires embedding equity safeguards into IMO and WTO processes, strengthening regional cooperation frameworks, and enhancing national legal capacities. In terms of concrete measures, developing countries need to actively participate in international rule-making processes and advocate for technological and financial support to mitigate these adverse impacts, thereby chart a course for marine sustainability.DiscussionThe global maritime system is undergoing a profound transformation that presents both risks and opportunities for vulnerable developing countries, including LLDCs, LDCs, and SIDS. To navigate this new landscape, these nations require robust legal and policy coordination to mitigate trade risks and promote sustainable shipping. However, a severe scarcity of locally driven, policy-relevant research perpetuates their vulnerability in global governance. The international community must therefore move beyond token inclusion and deliberately invest in building domestic research capacity for these vulnerable states, thereby amplifying their voices.